Workplace Incivility and Job Satisfaction: Mediation of Subjective Well-Being and Moderation of Forgiveness Climate in Health Care Sector - Muhammad Safdar Khan; Natasha Saman Elahi; Ghulam Abid (MDPI AG, 2021)
Our study investigates the role of subjective well-being and forgiveness climate between workplace incivility and job satisfaction. Drawing on conservation of resource theory, we proposed a model in which workplace incivility is associated with job satisfaction through subjective wellbeing, and forgiveness climate moderates this association. Data was collected through a survey method from 672 nurses and doctors in the health care sector at two different times. Respondents completed workplace incivility and subjective well-being scale at Time 1, and a forgiveness climate and job satisfaction scale at time 2. Findings through PROCESS Macros (Model 5) show that workplace incivility has a negative influence on job satisfaction and subjective well-being. Subjective well-being plays a mediating role in the negative effect of workplace incivility on job satisfaction. Moreover, forgiveness climate moderates the relationship between workplace incivility and job satisfaction. The implications for practice and research are discussed.